THE IMPERATIVE OF IRON AND STEEL COMPLEX – AJAOKUTA - Unuigboje, Alofoje (International Journal of Research -GRANTHAALAYAH, 2018)
Steel Complex constitutes the substratum of industrialization, without which attempts at industrial development remain a pipe dream, bleeding resources of a nation and ensuring the transfer of resources to the declination of developmental efforts.